The relationship between transformational and transactional leadership styles practiced by the foreman with job performance of production workers in Grand Banks Yacht Sdn. Bhd. - Tanurekga Raman, 1981-; Azlah Mohd. Ali, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2010)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2010